Technical efficiency of U.S. Western Great Plains wheat farms using stochastic frontier analysis. Issue 1 (31st December 2023) - Ji, Inbae; Vitale, Jeffrey D.; Vitale, Pilja P.; Adam, Brian D.
ABSTRACT: Technical efficiency (TE) is an important measure of farm performance. This study measured the TE of wheat farms across six states in the U.S. Western Great Plains based on production and farm management-specific variables. Significant factors positively influencing efficiency were insecticide use, farm size, and tillage. Alternatively, government payments, crop insurance, off-farm income, and crop share rates had negative effects on efficiency. Kansas and Oklahoma farms were more efficient than Nebraska and Wyoming farms in the sample. Average TE score of 0.56 indicates a substantial gap between average producers and the most efficient ones located near the TE frontier. Benchmarking the highly efficient farms provides best-management practices enabling less-efficient farms move closer to the efficient frontier. Extension specialists and collaboration among farms could transfer the skills and techniques through workshops, webinars, fact sheets, and social media pages.